The marginalization of poetry : language writing and literary history - Perelman, Bob (Book collections on Project MUSE., 1996)
Language writing, the most controversial avant-garde movement in contemporary American poetry, appeals strongly to writers and theorists interested in the politics of postmodernism and in iconoclastic poetic form. Drawing on materials from popular culture, avoiding the standard stylistic indications of poetic lyricism, and using nonsequential sentences are some of the ways in which language writers make poetry a more open and participatory process for the readers. Reading this kind of writing, however, may not come easily in a culture where poetry is treated as property of a special class. It is this barrier that Bob Perelman seeks to break down in this fascinating and comprehensive account of the language-writing movement. A leading language writer himself, Perelman offers insights into the history of the movement and discusses the political and theoretical implications of the writing - including postmodern fragmentation, the poetics of avant-garde formations, the politics of multicultural poetics, and gender and the avant-garde. He provides detailed readings of work by Lyn Hejinian, Ron Silliman, and Charles Bernstein, among many others, and compares it to a wide range of other contemporary and modern American poetry.